Protocol for individual participant data meta-analysis of interventions for post-traumatic stress. Issue 2 (15th February 2022) - Wright, Simonne Lesley; Karyotaki, Eirini; Bisson, Jonathan I; Cuijpers, Pim; Papola, Davide; Witteveen, Anke B; Seedat, Soraya; Sijbrandij, Marit
Abstract : Introduction: Several evidence-based treatments are effective for post-traumatic stress disorder (PTSD), yet a substantial proportion of patients do not respond or dropout of treatment. We describe the protocol for a systematic review and individual participant data meta-analysis (IPD-MA) aimed at assessing the effectiveness and adverse effects of psychotherapy and pharmacotherapy interventions for treating PTSD. Additionally, we seek to examine moderators and predictors of treatment outcomes. Method and analysis: This IPD-MA includes randomised controlled trials comparing psychotherapy and pharmacotherapy interventions for PTSD. PubMed, Embase, PsycINFO, PTSDpubs and CENTRAL will be screened up till the 11th of January 2021. The target population is adults with above-threshold baseline PTSD symptoms on any standardised self-report measure. Trials will only be eligible if at least 70% of the study sample have been diagnosed with PTSD by means of a structured clinical interview. The primary outcomes of this IPD-MA are PTSD symptom severity, and response rate. Secondary outcomes include treatment dropout and adverse effects. Two independent reviewers will screen major bibliographic databases and past reviews. Authors will be contacted to contribute their participant-level datasets. Datasets will be merged into a master dataset. A one-stage IPD-MA will be conducted focusing on the effects of psychological and pharmacological interventions on PTSD symptom severity, response rate, treatment dropout and adverse effects. Subsequent analyses will focus on examining the effect of moderators and predictors of treatment outcomes. These will include sociodemographic, treatment-related, symptom-related, resilience, intervention, trauma and combat-related characteristics. By determining the individual factors that influence the effectiveness of specific PTSD treatments, we will gain insight into personalised treatment options for PTSD. Ethics and dissemination: Specific ethics approval for an IPD-MA is not required as this study entails secondary analysis of existing anonymised data. The results of this study will be published in peer-reviewed scientific journals and presentations.